2021
DOI: 10.3389/fnhum.2021.762450
|View full text |Cite
|
Sign up to set email alerts
|

Gait Adaptation to a Phase-Specific Nociceptive Electrical Stimulation Applied at the Ankle: A Model to Study Musculoskeletal-Like Pain

Abstract: Introduction: Lower limb pain, whether induced experimentally or as a result of a musculoskeletal injury, can impair motor control, leading to gait adaptations such as increased muscle stiffness or modified load distribution around joints. These adaptations may initially reduce pain but can also lead to longer-term maladaptive plasticity and to the development of chronic pain. In humans, many current experimental musculoskeletal-like pain models are invasive, and most don’t accurately reproduce the movement-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Painful electrical stimulation has traditionally been used to induce transient pain 17,18 . More recently, this technique has been used to investigate whether motor adaptations are a purposeful strategy to reduce the noxious stimulation 19–21 . For instance, by modulating in real time the amplitude of the stimulation based on the load applied to the right leg on the ground, we showed that participants were able to decrease their perceived pain intensity by redistributing the amount of weight between legs 21 .…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Painful electrical stimulation has traditionally been used to induce transient pain 17,18 . More recently, this technique has been used to investigate whether motor adaptations are a purposeful strategy to reduce the noxious stimulation 19–21 . For instance, by modulating in real time the amplitude of the stimulation based on the load applied to the right leg on the ground, we showed that participants were able to decrease their perceived pain intensity by redistributing the amount of weight between legs 21 .…”
Section: Introductionmentioning
confidence: 89%
“…17,18 More recently, this technique has been used to investigate whether motor adaptations are a purposeful strategy to reduce the noxious stimulation. [19][20][21] For instance, by modulating in real time the amplitude of the stimulation based on the load applied to the right leg on the ground, we showed that participants were able to decrease their perceived pain intensity by redistributing the amount of weight between legs. 21 Together with the fact that painful electrical stimulation delivered as low-frequency sinusoidal waveforms results in minimal habituation over time, 21 this experimental pain model offers a unique opportunity to directly compare motor adaptation to tonic and movement-evoked pain.…”
Section: Introductionmentioning
confidence: 94%
“…For both groups, the intensity remained constant throughout the experiment. For more information regarding this experimental MSK-like pain protocol, see Bertrand-Charette et al ( 27 ).…”
Section: Methodsmentioning
confidence: 99%
“…Experimental pain intensity can be readily modulated based on the amplitude of electrical current [19][20][21][22], allowing for rapid changes in pain perceptions. Therein, pain can be induced based on movement mechanics in real time, such as plantar foot pressure during gait [23], ground reaction forces during standing balance [24], or wrist kinematics [20]. A limitation of this method is habituation with repeated or constant stimulation [25], but it appears this can be mitigated in the short term by using low frequency sinusoids [21,24,26].…”
Section: Introductionmentioning
confidence: 99%